Interactive Multimedia: The Benefits In Batik Art Learning (Universitas Negeri Semarang, 2022)
Many people believe that interactive multimedia can create the potential for a high-quality learning environment. However, in fact, many teachers at the primary school level have not used interactive multimedia in the batik learning. From the data in primary schools in Semarang, most teachers have not implemented interactive multimedia in batik learning. This study aims to explain the effectiveness of interactive multimedia use in batik learning. The quantitative method was an experimental method. The sampling employed cluster random sampling techniques, from SDN Sekaran 01 as an experimental group involving 26 students and SDN Sekaran 02 as a control group involving 27 students. The data collection techniques employed tests, non-tests, t-test data analysis and N-Gain.The results indicated that interactive multimedia was effective in terms of the average test result of the experimental group 79.19 and the average control group 73.20. The result of N-Gain experimental group was 0.21, included in the low category and the N-Gain of the control group was 0.38, included in the medium category; therefore, interactive multimedia can be applied in batik learning activities